MINORITY LANGUAGES IN KOSOVO - Krasniqi, Safet; Bajraktari, Halim (International Journal of Research -GRANTHAALAYAH, 2020)
The paper includes the legal aspect and political harmonization of human rights and freedom in the context of an analysis about the legitimate and executive function of the state of Kosovo. Guaranteeing civil rights it’s a part of and obligation that Kosovo institutions have, that are accorded in the legal structure of the fundamental human rights. This approach, mostly has to do with the majority community in Kosovo, that legally and politically are constitutional category.